2011
DOI: 10.1002/art.30421
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor C attenuates joint damage in chronic inflammatory arthritis by accelerating local lymphatic drainage in mice

Abstract: Objective To investigate if enhancement of joint lymphangiogenesis by injecting VEGF-C adeno-associated virus (AAV) into joints has therapeutic efficacy in chronic inflammatory arthritis in mice. Methods TNF transgenic (TNF-Tg) mice were used as a model of chronic inflammatory arthritis. Human VEGF-C was cloned into an AAV expression vector to generate AAV-VEGF-C. AAV-VEGF-C or control AAV-Luc was injected into joints of TNF-Tg mice. MRI and lymphatic imaging were used during the 4-months following injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
102
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 44 publications
8
102
3
Order By: Relevance
“…Recent studies in animals provide evidence that affecting lymphatic drainage by promoting the growth of lymphatic vessels can modulate inflammation 60, 61, 62, 63. Lymphatic vessel hyperplasia has been associated with hypercholesterolemia,42 but we show here that apoA‐I does not reduce vessel diameters.…”
Section: Discussioncontrasting
confidence: 44%
“…Recent studies in animals provide evidence that affecting lymphatic drainage by promoting the growth of lymphatic vessels can modulate inflammation 60, 61, 62, 63. Lymphatic vessel hyperplasia has been associated with hypercholesterolemia,42 but we show here that apoA‐I does not reduce vessel diameters.…”
Section: Discussioncontrasting
confidence: 44%
“…ApoA-I also reduced TNF-R1 signaling and conserved Prox-1 expression in LECs. These results were further corroborated in hTNFtg mice, 3,6,19 where the phenotype of the lymphatic vasculature of the diaphragm was normalized by apoA-I treatment. This suggests that apoA-I may regulate protective molecular pathways in lymphatic endothelium, and therefore, it is a potential therapeutic target with the capacity to improve lymphatic function and promote resolution of acute and chronic inflammatory states.…”
Section: Discussionsupporting
confidence: 52%
“…24 In addition, hTNFtg mice, a model of chronic inflammatory arthritis, exhibit decreased lymph flow from the joints compared with wild-type littermates. 6 Finally, TNF blockade in patients with rheumatoid arthritis and in experimental arthritis has been shown to promote lymphatic vessel formation and the resolution of chronic synovial inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The studies investigating AAV transduction in injured joints are limited with prior work focused more on rheumatoid arthritis (Pan et al, 1999;Goater et al, 2000;Zhou et al, 2011). Two groups used a transgenic mouse model that spontaneously develops arthritis due to tumor necrosis factor (TNF)-a overexpression (Goater et al, 2000;Zhou et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Two groups used a transgenic mouse model that spontaneously develops arthritis due to tumor necrosis factor (TNF)-a overexpression (Goater et al, 2000;Zhou et al, 2011). Goater et al (2000) reported increased AAV transduction efficiency with increased degree of the joint disease following an intra-articular injection of AAV, with synoviocytes as the primary target.…”
Section: Discussionmentioning
confidence: 99%